CICLO CE VIDA Y HABITOS DE Bracon kirkpatricki Wilkinson - Eraso Gudiño, Ana Lucia; León Martinez, Guillermo A.; Ramos Ordoñez, Armando (Revista de Ciencias Agrícolas, 1988)
El presente trabajo se realizó en el Centro Nacional de Investigaciones de "Palmira" Valle: ICA a 1.000 msnm a 24r59°C y 73,13% de humedad relativa. Se efectuaron estudios del ciclo de vida y hábitos de B. kirkpatricki W. (Hymenoptera: Branconidae) parásito de Anthonomus grandis B. y pectinophora gossypiella S. Además, se elaboró la tabla de fertilidad, encontrándose que la rata neta de reproducción (Ro) fue de 19,31 y la rata intrínseca de crecimiento (rm) de 0,18. ABSTRACT This research paper was elaborated at the National Center of Investigation "Palmira". The center belongs to the "Instituto Colombiano Agropecuario ICA" which is located at "Palmira" town to 1.000 meters above sea level. The laboratory conditions were 24,59°C and a relative average wet of 73,13%. It was studied the habits and life cycle of Braecon Kirk patricki (Wilkinson (Hymenoptera: Braconidae) wich is a parasitic of Anthonomus grandis Boheman and Pectinophora gossypiella Saunders. Besides it was elaborated the fertility table it is was found that the net rate of production (Ro) is 19,31 and the intrinsical rate of growing (rm) is 0.18.